Simulation-based design concept evaluation for ambulance patient compartments. (August 2015) - Kibira, Deogratias; Lee, Y Tina; Marshall, Jennifer; Feeney, Allison Barnard; Avery, Larry; Jacobs, Allie
To address the inadequacy of ambulance design standards, the Department of Homeland Security Science and Technology Directorate, the National Institute of Standards and Technology, the National Institute for Occupational Safety and Health, and BMT Designers and Planners have collaborated to develop new design standards for ambulance patient compartments. This paper presents a simulation-based approach to evaluate and guide improving patient compartment designs that conform to developed requirements for better performance and safety of ambulance users. Those requirements address hazards stemming from (1) the inability of providers to remain safely restrained while treating patients, and (2) the musculoskeletal damage from awkward body postures. An initial design was developed through the axiomatic design approach with inputs from stakeholders such as emergency medical service providers and ambulance manufacturers. The design was imported into a human task simulation tool. It was tested for performance to identify areas for further improvements, which resulted in a second design concept. This paper shows how computer simulation was used to evaluate the effectiveness of the two successive design concepts in enabling providers to perform a range of medical care tasks while remaining seated and restrained. We also evaluated the musculoskeletal effect of these designs on the providers. The results showed that using a simulation-based evaluation produced patient compartments that better meet user requirements when compared with traditional designs. This research produced a set of requirements and recommendations that we believe will lead to better design standards and guidelines for the next generation of ambulances.